Reconstruction of Nasal Defects with a Two-stage Nasolabial Flap - Isaraj, Sokol; Bendo, Lorela (Open Access Macedonian Journal of Medical Sciences, 2022)
Abstract Background Reconstruction of nasal defects represents a significant challenge in reconstructive surgery, due to nose’s delicate anatomy, combined with its functional and aesthetic relevance. Radical tumor excision, function preservation and a pleasing aesthetic outcome are the primary targets. The reconstructive approach will depend on the aesthetic subunit involved, size and depth of the defect. We describe our experience in the reconstruction of nasal skin defects of the tip, columella, alae, with a 2-stage nasolabial flap. Patients and Methods After institutional review board approval, a retrospective study was performed including consecutive patients (n=489) who underwent surgery for skin cancer of the nose, from 2016 to 2020 at the Service of Burns and Plastic Surgery, “Mother Theresa” University Hospital Center, of Tirana. Results The procedures were well tolerated and achieved good cosmetic results without complications. Conclusions The nasolabial 2-stage based flap is a well-established technique for nasal reconstruction after skin cancer removal. It represents one of the best methods for repair of extensive nasal defects, particularly for restoration of defects located on the tip, alae, or columella.